2018
DOI: 10.1017/s0007114518003458
|View full text |Cite
|
Sign up to set email alerts
|

Meat intake in relation to semen quality and reproductive hormone levels among young men in Spain

Abstract: The aim of this study was to assess the associations of intake of different types of meat with semen parameters and reproductive hormones in healthy young men. This cross-sectional study included 206 men, 18–23 years, from Southern Spain. All men completed a validated food frequency questionnaire, underwent a physical examination, and provided blood and semen samples. Multivariable linear regression was used to evaluate the associations between meat intake with semen quality parameters and reproductive hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Male infertility is an important disorder which can deleteriously impact both productivity and quality of life. Several studies have reported on the relationship between meat consumption and semen quality parameters as a proxy for male fertility (8,(17)(18)(19); however, there are discrepancies among ndings reported in the literature. Indeed, relatively small sample sizes in previous studies, in addition to the effect ethnic differences, might be the cause of inconclusive ndings, which highlights the necessity of further study to yield a reliable conclusion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Male infertility is an important disorder which can deleteriously impact both productivity and quality of life. Several studies have reported on the relationship between meat consumption and semen quality parameters as a proxy for male fertility (8,(17)(18)(19); however, there are discrepancies among ndings reported in the literature. Indeed, relatively small sample sizes in previous studies, in addition to the effect ethnic differences, might be the cause of inconclusive ndings, which highlights the necessity of further study to yield a reliable conclusion.…”
Section: Discussionmentioning
confidence: 98%
“…For example, red meat intake reduces the concentration and number of sperm. Fish consumption, on the other hand, is associated with higher sperm morphology (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the relationship between meat consumption and semen quality parameters as a proxy for male fertility [8,[20][21][22]; however, there are discrepancies among ndings reported in the literature. Indeed, relatively small sample sizes in previous studies, in addition to the effect of ethnic differences, might be the cause of inconclusive ndings, which highlights the necessity of further study to yield a reliable conclusion.…”
Section: Discussionmentioning
confidence: 98%
“…In several studies, a correlation between the intake of the food of animal origin and the incidence of some reproductive and health issues are reported. Thus, the connection between red meat intake and reduced semen motility was reported; however, shellfi sh consumption has the opposite effect [36]. In the study by Afeiche et al [37], semen of 189 donors from the US were analyzed in regard to the quality of consumed meat.…”
Section: Hormones In Food Of Animal Origin and Consumers' Healthmentioning
confidence: 99%